Risk Factors - Huxley, Rachel; Taylor, R.; Dobson, A. (2016)
© 2017 Elsevier Inc. All rights reserved. Risk factors for atherosclerotic cardiovascular disease (CVD) can be divided into three groups: fixed (nonmodifiable), major modifiable, and other factors. Rather than showing evidence of a step function, the relationship between cardiovascular risk and each of the major modifiable factors - smoking, blood pressure, blood lipids, and limited physical activity - is continuous and graded. Dichotomizing individuals into 'normal' and 'at-risk' groups ignores the fact that the lifestyles of almost all members of the community could be improved to reduce their risk of CVD. The pressing challenge is to broaden the understanding and application of this principle among both health professionals and policy makers.